WHY THE RICH ARE GETTING RICHER : What Is Financial Education...Really? - Kiyosaki, Robert T, 1947-
In this book, the reader will learn why the gap between the rich and everyone else grows wider; why savers are losers; why debt and taxes make the rich richer; why traditional education actually causes many highly educated people - such as Robert's po